My music my way : a case study of identity contestation among Singaporean musicians - Dcruz, Nigel Jude (2012)
In the era of late modernity, the mass media's moral panic machinery has centered its attention on youth cultures which under the lens of music have formed patterns for social identification and grouping. This patterns have been identified by nation states as a cause for social and moral disorder. This paper argues for Singapore musicians to be seen as a heterogeneous group of individuals, with differing opinions, motivations and experiences and agency given their relatively disadvantaged position. This paper examines the identity formation of Singaporean musicians and views their struggles through experiences told. The paper ends with strategies used by Singaporean musicians to resist, negotiate and challenge the identity placed on them by the state, society and their families.